A redescription of Anomaloglossus praderioi (La Marca, 1998) (Anura: Aromobatidae: Anomaloglossinae), with description of its tadpole and call - Philippe J.R. Kok (Papéis Avulsos de Zoologia, 2010)
Anomaloglossus praderioi was originally described as Colostethus praderioi by E. La Marca in 1998 on the basis of two male specimens. The present paper provides a redescription of the species on the basis of new material from Maringma Tepui in Guyana and an additional specimen from Sierra de Lema in Venezuela. The redescription includes descriptions of the tadpole and vocalisation. Anomaloglossus praderioi is a medium-sized species mainly distinguished from its known congeners in having Fingers I, II and IV equal in length, the tip of Finger IV barely reaching the base of the distal subarticular tubercle on Finger III when fingers are adpressed, Fingers II and III with preaxial keel-like lateral folds, toes basally webbed with folded flaplike fringing except on Toes IV-V, symmetrical cloacal tubercles present, thin pale dorsolateral stripe present from tip of snout to tip of urostyle, ventrolateral stripe inconspicuous, never straight, oblique lateral stripe absent, throat in male grey to very dark grey, almost solid black, with black blotches, throat in female bright orange, almost immaculate. The tadpole is dark brown to black, exotrophic, benthic, LTRF 2(2)/3. The advertisement call consists of long trains of a single note repeated at a rate of 61-76 notes/min with a dominant frequency ranging from 3,562 to 3,856 Hz. The species is reported from eastern Venezuela and western Guyana and inhabits montane medium-canopy forest at elevations between 1,310-1,950 m above sea level. Anomaloglossus praderioi fue originalmente descrito como Colostethus praderioi por E. La Marca en 1998 con dos ejemplares machos. El presente artículo ofrece una redescripción detallada de la especie basada en nuevos ejemplares de Maringma Tepui, en Guyana y ejemplares adicionales de la Sierra de Lema, en Venezuela. La redescripción incluye la vocalización y descripción del renacuajo. Anomaloglossus praderioi es de tamaño mediano y se distingue principalmente de sus congéneres por los siguientes caracteres: los dedos I, II y IV con igual longitud; punta del dedo IV apenas llega a la base del tubérculo subarticular distal del dedo III, cuando estos son colocados juntos; dedos II y III con la quilla preaxial y pliegues laterales; dedos de los pies palmeados basalmente, excepto en los dedos IV-V; simétricos tubérculos cloacales presentes; franja delgada dorsolateral de color pálido, la cual va desde la punta del hocico hasta la punta de urostilo; banda ventrolateral inconspicua, nunca recta; banda lateral oblicua ausente. Macho con garganta de color gris a gris muy oscuro, casi negro uniforme. En hembras la garganta es de color naranja brillante, casi inmaculada. La larva es castaño oscuro a negro, de hábitos exotróficos y bentónicos, LTRF 2 (2)/3. La llamada de advertencia consiste de largas series de una nota sencilla repetida a un ritmo de 61-76 notes/min con una frecuencia dominante que va desde 3,562 a 3,856 Hz. La especie queda registrada para el sureste de Venezuela y oeste de Guyana, habitando bosques montanos con cobertura media en elevaciones entre los 1,310-1,950 m s.n.m.